The Effectiveness of ReadTheory.org in Improving EFL Students’ Reading Comprehension - Nabila Putri, Adelia; Anggia, Helta (Journal of English Teaching, Literature, and Applied Linguistics, 2025)
This study investigates the usefulness of ReadTheory in enhancing EFL students’ reading comprehension. Due to their poor vocabulary proficiency and low interest in traditional reading materials, Indonesian senior high school students continue to struggle greatly with reading comprehension. This study employed a quasi-experimental design involving eleventh-grade students at SMA Gajah Mada Bandar Lampung, who were divided into two groups: an experimental group using ReadTheory and a control group using printed textbooks. Pre-tests and post-tests were used to gather data, and paired-sample and independent-sample t-tests were used for analysis. According to the findings, the experimental group improved their reading comprehension much more than the control group (p <.05). Students were able to interact with reading materials at suitable levels of difficulty because of ReadTheory's interactive and adaptive capabilities, which resulted in more steady learning gains. These results imply that ReadTheory (ReadTheory.org) is a useful online resource for improving the reading comprehension of EFL students and may be suggested as a substitute teaching method in secondary school settings.